2007
DOI: 10.1016/j.susc.2007.04.218
|View full text |Cite
|
Sign up to set email alerts
|

Electric conductance of metal nanowires at mechanically controllable break junctions under electrochemical potential control

Abstract: We have developed the mechanically controllable break junction setup with an electrochemical cell (EC-MCBJ) to measure the electric conductance of metal nanowires under electrochemical potential control. The electric conductance of Au nanowires was investigated in 0.1 M Na 2 SO 4 solution using EC-MCBJ. The conductance of the Au nanowires was quantized in units of G 0 (=2e 2 /h), showing clear features in the conductance histogram. The atomic contact with a specific conductance value was kept for more than 5 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…An important example is conductance quantization in nanowire systems. 1 Metal nanowires on an atomic scale, spoken of as atomic contacts, have been fabricated mainly by three techniques: scanning tunneling microscopy break junction (STM-BJ), [2][3][4] mechanically controllable break junction, 5,6 (MCBJ) and electrochemistry. 7,8 The phenomenon occurs when the diameter of the nanowire is comparable to the electron Fermi wavelength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important example is conductance quantization in nanowire systems. 1 Metal nanowires on an atomic scale, spoken of as atomic contacts, have been fabricated mainly by three techniques: scanning tunneling microscopy break junction (STM-BJ), [2][3][4] mechanically controllable break junction, 5,6 (MCBJ) and electrochemistry. 7,8 The phenomenon occurs when the diameter of the nanowire is comparable to the electron Fermi wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…An important example is conductance quantization in nanowire systems . Metal nanowires on an atomic scale, spoken of as atomic contacts, have been fabricated mainly by three techniques: scanning tunneling microscopy break junction (STM-BJ), mechanically controllable break junction, , (MCBJ) and electrochemistry. , The phenomenon occurs when the diameter of the nanowire is comparable to the electron Fermi wavelength . If, in addition, the nanowire is shorter than the electron mean free path, the electrons are transported ballistically along the nanowires, and the conductance is given by the Landauer formula, where T i is the transmission probability of the i th conductance channel, e the electron charge, and h the Planck constant.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an adhesive coated on 8 × 8 AM-PDMS demonstrated a significantly higher reduction in adhesion strength when compared to the adhesive coated on 16 × 16 AM-PDMS (Figure S17). The wire diameter for 8 × 8 AM (diameter = 0.028″) was significantly higher when compared to that of the 16 × 16 AM (diameter = 0.018″), which resulted in a significant increase in the level of recorded electrical current. , These results collectively indicated that the level of electrical current passing through the adhesive interface has a significant impact on the rate of adhesive deactivation.…”
Section: Resultsmentioning
confidence: 99%
“…An exemplary conductance-over-time measurement is shown in Figure 4A. The data from Figure 4A are plotted as a histogram in Figure 4B, showing increased occurrences of values at or near integer multiples of G 0 [28][29][30]. Such a quantized decrease of the conductance is expected for break junctions.…”
Section: Electrical Measurementsmentioning
confidence: 93%